P09.12 Hereditary homozygosity and allelic imbalance of HLA as common immune escape mechanisms in esophageal adenocarcinoma. (21st September 2022) - Garcia Marquez, MA; Thelen, M; Bauer, E; Wennhold, K; Lehmann, J; Keller, D; Maas, L; Nicolik, M; George, J; Zander, T; Schroeder, W; Müller, P; et al.
Abstract : Background: The human leukocyte antigen (HLA) genotype of an individual defines the repertoire of peptides which can be presented to T cells. In the tumor microenvironment, neoantigen presentation can be abrogated by alterations ofHLA class I molecules, which have a direct impact in immune surveillance. This study aims to elucidate the impact of hereditary homozygosity and imbalanced expression of HLA-I loci on the repertoire of immunogenic peptides that are presented in esophago-gastric adenocarcinoma patients (EGA). Materials and Methods: High-resolution clinical-grade HLA-genotyping was performed using the NGS method (n=80). Whole exome sequencing (WES) was done on tumor and blood (n=39) to call for somatic mutations. The amount of potential high affinity binders derived from 10 tumor-associated antigens (TAAs) frequently expressed in EGA and non-synonymous mutations obtained from WES data were determined using an in-silico approach for MHC-binding (IEDB.org). Gene expression profiling was done with 3`RNAseq (n=39). Whole RNAseq data was used to detect imbalanced or loosed expression of HLA-A/B/C alleles (n=19). Results: We compared the frequency of HLA homozygosity in EGA patients to an HLA-matched reference population derived from a large cohort of bone marrow donors (n=7.615). We demonstrate that homozygosity of HLA-I loci is significantly enriched in the germline of EGA patients compared to the control population (35% vs. 19%, corresponding to an odds ratio (OR) for homozygosity of 2.282 (95% CI 1.442–3.615, p<0.001)). We then aimed to estimate the influence of HLA-homozygosity in the context of tumor immune surveillance. Predictions by IEDB analysis resource tool indeed showed a reduced repertoire of high and moderate-affinity MHC-binders (both TAA-derived and mutation-derived peptides) in the homozygous cohort. Our findings demonstrate a reduced amount of potentially immunogenic peptides in EGA patients with HLA-homozygosity for at least one locus, which may result in impaired cancer immunosurveillance. In line with this observation, artificial restoration of the genotype of homozygous patients to a heterozygous genotype, resulted in a set of predicted good-binding peptides of comparable size to the heterozygous cohort. While 35% of EGA patients showed germline homozygosity of HLA-I loci, quantification of allele-specific expression of HLA-I revealed altered expression in 9 out of 12 heterozygous patients (75%). 3 of these patients showed complete loss of heterozygosity, whereas the others had altered expression of one or two HLA-I molecules. The allelic imbalance was significantly higher in heterozygous compared to homozygous were only 2 patients showed altered expression of one HLA-I molecule (28.6%, p=0.0240). None of the patients with allelic imbalance carried genetic mutations associated with HLA-I genes, underlying epigenetic regulation. Conclusions: The high frequency of genomic HLA-I homozygosity observed in the EGA cohort suggests that limitation of neoantigen presentation might have a role during EGA development and may reflect an increased cancer risk for these patients. Moreover, the results herein highlight that despite having a complete set of HLA-I alleles on a genomic level, the majority of EGA patients carry allelic imbalance that limit the repertoire of neoantigens for presentation to immune cells. Disclosure Information: M.A. Garcia Marquez: None. M. Thelen: None. E. Bauer: None. K. Wennhold: None. J. Lehmann: None. D. Keller: None. L. Maas: None. M. Nicolik: None. J. George: None. T. Zander: None. W. Schroeder: None. P. Müller: None. C. Bruns: None. R. Thomas: None. B. Gathof: None. A. Quaas: None. A.M. Hillmer: None. M. Peifer: None. M. von Bergwelt-Baildon: C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; Astellas, Roche, MSD. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; BMS. H.A. Schlößer: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Astra Zeneca.